TWO SIDED MARKETS – HOW TO GENERATE VALUE FROM THEM - Issac K Varghese; Mani P Sam (Universitas Kuningan, 2020)
The article provides insights on two sided markets. Two sided markets ae gaining momentum in the economy that’s relying more and more on cashless mode. It also talks about the way value is generated on platforms for both the sides. The article highlights the effect of networks on value creation. The cost management of these platforms can be done by using activity based costing. The article also throws light on the need for eliminating non value-adding activities.